Arteterapia jako forma terapii i wsparcia rozwoju dzieci ze specjalnymi potrzebami rozwojowymi i edukacyjnymi. Od uwag teoretycznych do projektów działań arteterapeutycznych, z pytaniem o tożsamość arteterapii w tle - Nieduziak, Edyta M. (Warstwy, 2021)
The article discusses using art therapy in education, in particular while working with pupils with special educational needs. Starting this discussion is a point of departure to answer the question about the specific nature of art therapy in this area of practice and research. It is important inasmuch as it can serve to create programs of art therapy studies which should include themes from special needs education understood as education of people threatened with social exclusion. The author indicates three basic challenges of art therapy in education: knowledge and understanding of children’s/pupils’ diagnoses, using diverse artistic means, using evaluation tools. She illustrates this with three examples of art therapy projects prepared by art therapy students.